Multifunctional nanozyme-reinforced copper-coordination polymer nanoparticles for drug-resistance bacteria extinction and diabetic wound healing - Jiahui Zhao; Tengfei Xu; Jichao Sun; Haitao Yuan; Mengyun Hou; Zhijie Li; Jigang Wang; Zhen Liang (Biomaterials Research, 2023)
Abstract Background Drug-resistant bacterial infections in chronic wounds are a persistent issue, as they are resistant to antibiotics and can cause excessive inflammation due to generation of reactive oxygen species (ROS). An effective solution would be to not only combat bacterial infections but also scavenge ROS to relieve inflammation at the wound site. Scaffolds with antioxidant properties are attractive for their ability to scavenge ROS, and there is medical demand in developing antioxidant enzyme-mimicking nanomaterials for wound healing. Methods In this study, we fabricated copper-coordination polymer nanoparticles (Cu-CPNs) through a self-assembly process. Furthermore, ε-polylysine (EPL), an antibacterial and cationic polymer, was integrated into the Cu-CPNs structure through a simple one-pot self-assembly process without sacrificing the glutathione peroxidase (GPx) and superoxide dismutase (SOD)-mimicking activity of Cu-CPNs. Results The resulting Cu-CPNs exhibit excellent antioxidant propertiesin mimicking the activity of glutathione peroxidase and superoxide dismutase and allowing them to effectively scavenge harmful ROS produced in wound sites. The in vitro experiments showed that the resulting Cu-CPNs@EPL complex have superior antioxidant properties and antibacterial effects. Bacterial metabolic analysis revealed that the complex mainly affects the cell membrane integrity and nucleic acid synthesis that leads to bacterial death. Conclusions The Cu-CPNs@EPL complex has impressive antioxidant properties and antibacterial effects, making it a promising solution for treating drug-resistant bacterial infections in chronic wounds. The complex’s ability to neutralize multiple ROS and reduce ROS-induced inflammation can help relieve inflammation at the wound site. Graphical Abstract Schematic illustration of the ROS scavenging and bacteriostatic function induced by Cu-CPNs@EPL nanozyme in the treatment of MRSA-infected wounds.